Resveratrol induces apoptosis by modulating the reciprocal crosstalk between p53 and Sirt-1 in the CRC tumor microenvironment - Brockmueller, Aranka; Buhrmann, Constanze; Shayan, Parviz; Shakibaei, Mehdi (Frontiers in Immunology, 2023)
Background: P53 represents a key player of apoptosis-induction in cancers including colorectal cancer (CRC) that ranks third worldwide in cancer prevalence as well as mortality statistics. Although a proapoptotic effect of resveratrol has been repeatedly proven in CRC cells, its pathway mechanisms are not completely understood, as there are controversial statements in the literature regarding its activation or inhibition of the counteracting proteins Sirt-1 and p53.Materials and Methods: CRC cells as wild-type (HCT-116 WT) or p53-deficient (HCT-116 p53 -/-) were cultured using multicellular tumor microenvironment (TME) cultures containing T-lymphocytes and fibroblasts to elucidate the role of p53/Sirt-1 modulation in resveratrol's concentration-dependent, pro-apoptotic, and thus anti-cancer effects.Results: Resveratrol dose-dependently inhibited viability, proliferation, plasticity as well as migration, and induced apoptosis in HCT-116 WT more effectively than in HCT-116 p53 -/-cells. Moreover, resveratrol stimulated Sirt-1 expression when administered at low concentrations (<5µM) but suppressed it when added at high concentrations (10>10µM) to CRC-TME. In parallel, similar to knockdown of Sirt-1 at the mRNA level, treatment with high-concentration resveratrol boosted the acetylation of p53, the expression of p21, Bax, cytochrome C, caspase-3, and ultimately induced apoptosis in CRC WT but not in CRC p53 -/-cells. Notably, increasing concentrations of resveratrol were found to promote hyperacetylation of p53 and FOXO3a as post-translational substrates of Sirt-1, indicating a negative regulatory loop between Sirt-1 and p53.These results demonstrate for the first time, a negative reciprocal crosstalk between the regulatory circuits of p53 and Sirt-1, consequently, apoptosis induction by higher resveratrol concentrations in CRC-TME.